2020
DOI: 10.1002/berj.3677
|View full text |Cite
|
Sign up to set email alerts
|

Recognising and responding to radicalisation at the ‘frontline’: Assessing the capability of school teachers to recognise and respond to radicalisation

Abstract: Governments across the west have put teachers at the forefront of efforts to tackle radicalisation of young people based on their proximity to potentially vulnerable students. This has proven controversial, as critics claim that this securitises teachers’ work and that they cannot be expected to accurately identify and respond to extremism. Despite investment in P/CVE teacher training, research to assess teachers’ competence to identify signs of radicalisation and to respond in an appropriate manner is scarce.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 37 publications
1
15
2
Order By: Relevance
“…The teachers reported on three patterns of risk factors (personal, religious and socio‐political) that might trigger students' religious extremism. They seem more confident, compared to previous studies, to evaluate signs of radicalisation and to respond to them as part of their safeguarding duty (Moffat & Gerard, 2019; Parker et al, 2021). These patterns, the author argues, may function separately or in combination.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The teachers reported on three patterns of risk factors (personal, religious and socio‐political) that might trigger students' religious extremism. They seem more confident, compared to previous studies, to evaluate signs of radicalisation and to respond to them as part of their safeguarding duty (Moffat & Gerard, 2019; Parker et al, 2021). These patterns, the author argues, may function separately or in combination.…”
Section: Discussionmentioning
confidence: 83%
“…Religious education teachers, because of their intimate relationships with students, are well placed to identify and prevent religious extremism in schools and the larger society (Parker et al, 2021). This study explores Islamic education teachers' perspectives on religious extremism among their Arab Muslim students in middle and high schools in Israel.…”
Section: Introductionmentioning
confidence: 99%
“…From the students' perspective, the fears of being labelled as radicalised have limited the scope, depth, and possibilities of educational discussions on sensitive topics that students want to engage in class and prevented some of them from seeking psychological support from the school's well-being personnel in the fear of stigma [71][72][73][74][75]. Overall, the PVE-E policies approached from a monitoring perspective may heavily undermine the trust of the students and their families in the teachers and the education system as a place of support and help, and have a long-term toll on the well-being of the students [2,5,68,76]. The lack of trust and higher thresholds for seeking socio-emotional support may indeed hinder the general feeling of safety in educational institutions and increase the risk of radicalisation.…”
Section: Schools As Safe Spaces: Thinking Through Dangerous Territorymentioning
confidence: 99%
“…The challenges these developments pose for societies and their educational institutions are growing and becoming more complex [2][3][4][5]. As possible approaches for the prevention of violent attitudes, radicalisation, and extremism in education, authorities and scholars from various fields have suggested, for example, peace education [6], citizenship education [7], religious education [8], or fostering of national values [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous studies highlight teachers' puzzlement about these suggested duties or responsibilities regarding the prevention of radicalization (Parker, Lindekilde & Gøtzsche-Astrup, 2020;Mattsson & Johansson, 2020;Ragazzi, 2017;van San, Sieckelinck & de Winter, 2013). Many questions remain open especially regarding the objectives and pedagogical implementation of such responsibilities, which, together with the vague definitions of the key concepts, make tackling this mission challenging (Sjøen & Mattsson, 2020;Mattsson & Säljö, 2017;Ragazzi, 2017;Grossman et al, 2017;Christodoulou, 2020).…”
Section: Modes Of Resilience and Threshold Of Adversitymentioning
confidence: 99%